Airborne transmission of severe acute respiratory syndrome coronavirus‐2 to healthcare workers: a narrative review. (8th May 2020) - Wilson, N. M.; Norton, A.; Young, F. P.; Collins, D. W.
Summary: Healthcare workers are at risk of infection during the severe acute respiratory syndrome coronavirus‐2 pandemic. International guidance suggests direct droplet transmission is likely and airborne transmission occurs only with aerosol‐generating procedures. Recommendations determining infection control measures to ensure healthcare worker safety follow these presumptions. Three mechanisms have been described for the production of smaller sized respiratory particles ('aerosols') that, if inhaled, can deposit in the distal airways. These include: laryngeal activity such as talking and coughing; high velocity gas flow; and cyclical opening and closure of terminal airways. Sneezing and coughing are effective aerosol generators, but all forms of expiration produce particles across a range of sizes. The 5‐μm diameter threshold used to differentiate droplet from airborne is an over‐simplification of multiple complex, poorly understood biological and physical variables. The evidence defining aerosol‐generating procedures comes largely from low‐quality case and cohort studies where the exact mode of transmission is unknown as aerosol production was never quantified. We propose that transmission is associated with time in proximity to severe acute respiratory syndrome coronavirus‐1 patients with respiratory symptoms, rather than the procedures per se. There is no proven relation between any aerosol‐generating procedure with airborne viral content with the exception of bronchoscopy and suctioning. The mechanism for severe acute respiratory syndrome coronavirus‐2 transmission is unknown but the evidence suggestive of airborne spread is growing. We speculate that infected patients who cough, have high work of breathing, increased closing capacity and altered respiratory tract lining fluid will be significant producers of pathogenic aerosols. We suggest several aerosol‐generating procedures may in fact result in less pathogen aerosolisation than a dyspnoeic and coughing patient. Healthcare workers should appraise the current evidence regarding transmission and apply this to the local infection prevalence. Measures to mitigate airborne transmission should be employed at times of risk. However, the mechanisms and risk factors for transmission are largely unconfirmed. Whilst awaiting robust evidence, a precautionary approach should be considered to assure healthcare worker safety.